Community-Acquired Pseudomonas Aeruginosa Wrist Joint Arthritis in a Child - A Case Report - Jangid, Manoj Kumar; Selim, Mohamad Ahmed (Journal of Nepal Paediatric Society, 2020)
Pseudomonas aeruginosa is a rare cause of bone and joint infection in an immunocompetent child. Rapid diagnosis and prompt therapy are required to prevent serious joint damage. We hereby present our experience with a case of septic arthritis involving distal radioulnar joint with associated distal radius osteomyelitis in a previously healthy six years old girl who presented with fever, swelling and pain of the right lower forearm. Pseudomonas aeruginosa was isolated from both joint fluid and blood. The child was successfully treated with a combination of surgical debridement and two weeks of intravenous and four weeks of oral antibiotic therapy.